The Role of Lecturers in Building Student Resilience - Romli, Ahmad Syaifuddin; Luayyin, Reza Hilmy; Billah, Ana (International Journal of Multidisciplinary Research of Higher Education, 2025)
Lecturers have a role in the academic field and building student resilience. Academically, lecturers are obliged to teach, research and serve. In addition, students really need the role of lecturers in building student resilience. The purpose of this study is to provide knowledge to lecturers that in addition to teaching, researching and serving, lecturers also have a role in building student resilience. This research uses a qualitative descriptive approach with SWOT analysis. The results of the study said that there were six student respondents who became student resilience in lectures. Factors that become student resilience in lectures from several respondents can be seen that student resilience is related to finance in paying tuition fees, self-development, mental heal and motivation. Meanwhile, at the Ahmad Dahlan Institute campus, the role of lecturers in building student resilience consists of four types, namely a) Character Development, b) Academic Guidance, c) Emotional Support and d) Stress Management. In addition, the role of lecturers in building student resilience has four categories, namely i) Integrative-Collaborative, ii) Innovative-Communicative, iii) Innovative-Collaborative and iv) Integrative-Communicative.